Synthesis and DNA‐Binding Studies of A New Cyclic Dimeric Symmetrical Pseudo‐Turn Mimetic. Issue 7 (20th February 2018) - Banerji, Biswadip; Chatterjee, Satadru; Killi, Sunil Kumar; Srinivas, D.; Prodhan, Chandraday; Katarkar, Atul; Chaudhuri, Keya
Abstract: A new dimeric cyclic 24 member symmetrical turn analogue was synthesized efficiently by an intramolecular Heck reaction. This facile reaction has produced selectively a single dimeric product having two sets of intramolecular hydrogen bonds (IHB) at the two ends of it. Different experimental studies have unambiguously proved the presence of a pseudo‐turn like structure. Furthermore, it was shown that this molecule binds to the minor groove of DNA just like a known minor groove binder, DAPI (4′, 6‐diamidino‐2‐phenylindole). Abstract : In the present study, a 24‐member symmetrical, cyclic dimeric turn like structure was synthesized by an intra molecular heck reaction. The molecule shows two consecutive 8‐member intra molecular hydrogen bonds at the two ends, which helps the structure to adopt a dimeric pseudo turn like structure. The molecule has been shown to bind DNA minor groove like DAPI (4′, 6‐diamidino‐2‐phenylindole).